[57] Bacteriological analysis of urinary stones: correlation with preoperative cytobacteriological examination of urine - Amine Saouli (Taylor & Francis Group, 2018)
Objective: To analyse the bacteriological correlation between preoperative cytobacteriological examination of urine (CBEU) and urinary calculi, and to evaluate the impact of chemical nature on the bacteriological stones. Methods: This was a prospective single-centre study including 42 patients who underwent urolithiasis surgery between January and April 2018. Bacteriological culture of the removed stones was systematic. Mean comparisons were made by the Pearson chi-square test and Fisher’s test for qualitative variables, with statistical significance set at P < 0.05. Results: The average age of our series was 56 years, with a male predominance of 83.3%. Bladder opening was performed in 45.2% of our patients. The rate of urinary colonisation was 33.3% (14/42). The rate of infected stones was 35.7%. Of the identified pathogens, Escherichia coli was found in 40% of the infected stones, followed by Enterococcus faecalis (20%), and Staphylococcus coagulase negative and Pseudomonas aeruginosa (13.3%). There was a significant correlation (P < 0.001) between preoperative CBEU and bacteriological analysis of the stones. The infected stones were principally calcium oxalate monohydrate and struvite (P = 0.03, P = 0.01). Conclusion: There is a significant correlation between the bacteriological culture of urinary stones and preoperative CBEU results. A negative preoperative CBEU can guarantee the sterility of urinary calculi in 89.2% for avoiding postoperative infectious complications after surgical manipulation of these stones.